Impaired Motor Competence in Children With Transplanted Liver. Issue 6 (June 2015) - Almaas, Runar; Jensen, Unn; Loennecken, Marianne C.; Tveter, Anne T.; Sanengen, Truls; Scholz, Tim; Holm, Inger
Abstract Objectives: Although reduced cognitive function has been demonstrated after liver transplantation in children, few data are available concerning motor competence. Methods: Thirty-five children ages 4 to 12 years were tested using Movement Assessment Battery for Children (M-ABC) test at a median of 5.1 (3.9–6.9) years after liver transplantation and compared with reference material of healthy children. Results: Children with transplantation had worse M-ABC score 8.0 (interquartile range 5.0–11.5), compared with healthy children 3.5 (1.0–6.0) (P < 0.0001). All of the subscores (manual dexterity [P < 0.0001], ball skills [P = 0.0037], and balance [P = 0.0032]) were significantly worse in the children with liver transplantation compared with the healthy reference group. Twenty-nine percent of the children with liver transplantation had impaired motor competence, compared with 9% of a healthy reference group. Seventeen of the patients with transplantation were retested 1 year later, and 11 were tested 4 years later with no changes in total M-ABC score. Ball skill competence was worse 4 years after first assessment (P = 0.013). For children with transplantation and cholestatic liver disease (n = 26), renal function was a significant predictor for total M-ABC score (P = 0.018). Conclusions: Children with liver transplantation had impaired motor competence compared with healthy children. Ball skills developed adversely several years after liver transplantation, and motor competence did not improve with time after transplantation. Renal function was a significant predictor for motor competence in children with liver transplantation and cholestatic liver disease.